Sustainable utilization of deinking paper mill sludge for the manufacture of building bricks. (10th December 2018) - Singh, S.K.; Kulkarni, Shilpa; Kumar, Vivek; Vashistha, Prabhat
Abstract: Building bricks were produced by utilizing deinking paper mill sludge (DPMS) and alluvial soil by varying percentage of sludge at different firing temperatures. Different mix proportions were prepared with 0%, 5%, 10%, 15%, 20%, 25% and 30% of DPMS incorporation in alluvial soil by weight. Three firing temperatures of 900 °C, 950 °C and 1000 °C were investigated to simulate the typical condition of kiln. The density, firing shrinkage, water absorption, efflorescence, apparent porosity, compressive strength and thermal conductivity of the bricks were determined. The XRD and microstructural analysis of brick specimens were also studied. The optimum firing temperature was 950 °C. The thermal conductivity decreases with increase in percentage of deinking paper mill sludge. It was found that 15% deinking paper mill sludge gives optimum strength at firing temperature of 950 °C. Developed bricks satisfy the requirements of class 10 of Bureau of Indian Standards (BIS), in terms of efflorescence, compressive strength and water absorption. Thermal conductivity results show that the developed brick was thermally more insulated than the conventional bricks and can be used as alternative to conventional bricks. This will address the issue of waste management through cleaner production and show the ways towards sustainable, economical and energy efficient construction. Highlights: Building bricks were developed utilizing deinking paper mill sludge (DPMS) & soil. Maximum level of DPMS in production brick is 15% at firing temperature of 950 °C. The developed bricks satisfies the requirement of class 10 bricks of BIS. Developed bricks are sustainable and thermally insulated.